2020
DOI: 10.1177/0018720820959958
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Driver Perception: Combining Eye-Tracking and Automated Road Scene Perception

Abstract: Objective To investigate how well gaze behavior can indicate driver awareness of individual road users when related to the vehicle’s road scene perception. Background An appropriate method is required to identify how driver gaze reveals awareness of other road users. Method We developed a recognition-based method for labeling of driver situation awareness (SA) in a vehicle with road-scene perception and eye tracking. Thirteen drivers performed 91 left turns on complex urban intersections and identified images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
1
12
2
Order By: Relevance
“…Head movement features have been used in a few studies assessing whether a patient is under stress-they are usually more frequent, faster, and more significant [10]. The application of electrooculography (EOG) in the design of braincomputer interfaces and activity recognition has been described in several studies [12][13][14][15][16]. Electrooculography (EOG) is a technique for measuring the resting electrical potential between the cornea and retina of the human eye by registering the electrical signal via electrodes placed around the eyes [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Head movement features have been used in a few studies assessing whether a patient is under stress-they are usually more frequent, faster, and more significant [10]. The application of electrooculography (EOG) in the design of braincomputer interfaces and activity recognition has been described in several studies [12][13][14][15][16]. Electrooculography (EOG) is a technique for measuring the resting electrical potential between the cornea and retina of the human eye by registering the electrical signal via electrodes placed around the eyes [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by Niwa et al [9] and Doniec et al [17] are the only known study on drivers' behavior which used JINS MEME smart glasses. Another recent study on recognizing the gaze on the left turn was conducted by Stapel et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these paradigms have been extended to tasks such as scene perception. Recarte and Nunes (2000) and Stapel et al (2020), for instance, have used the boundary method to analyze eye movements during driving tasks and thereby assess the effect of driver awareness on gaze behavior. In particular, Recarte and Nunes (2000) have observed that distracted drivers had higher fixation durations, higher pupil dilations, and lower fixation counts in the mirror/speedometer AOIs compared to control subjects.…”
Section: Psychologymentioning
confidence: 99%